2004
DOI: 10.1016/j.pain.2004.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of non-specific musculoskeletal pain in preadolescents: A prospective 4-year follow-up study till adolescence

Abstract: Musculoskeletal pain is common in children but studies on the outcome and predictive factors for persistence/recurrence of these symptoms are scarce. A baseline cross-sectional survey of 1,756 schoolchildren (mean age 10.8) identified 564 (32.1%) children with musculoskeletal pain. At baseline, these children were evaluated using a structured questionnaire and examined for hypermobility and physical fitness. The children were re-evaluated after one year, and four years (at adolescence) using the same pain ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
144
2
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 33 publications
13
144
2
13
Order By: Relevance
“…Insufficient quantity and quality of sleep could well be related to the increased prevalence of musculoskeletal pains. Some early studies suggest that tiredness, difficulties in falling asleep, waking up at night and other sleep problems are risk factors for musculoskeletal pains [10,42,47,52]. A cohort-based, long-term follow-up study among adults showing that sleep disturbances predict hospitalizations for back disorders [21] confirmed earlier observations, although the results may have been confounded by occupational factors.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Insufficient quantity and quality of sleep could well be related to the increased prevalence of musculoskeletal pains. Some early studies suggest that tiredness, difficulties in falling asleep, waking up at night and other sleep problems are risk factors for musculoskeletal pains [10,42,47,52]. A cohort-based, long-term follow-up study among adults showing that sleep disturbances predict hospitalizations for back disorders [21] confirmed earlier observations, although the results may have been confounded by occupational factors.…”
Section: Introductionsupporting
confidence: 52%
“…The majority of previous findings are, nevertheless, consistent with our results. Among longitudinal studies, daytime tiredness predicted musculoskeletal pains in a 1-year follow-up of 363 children [28], and waking up at night predicted musculoskeletal pains among girls in a 4-year follow-up of the same population [10]. Difficulty in falling asleep increased the risk of low back pain in a 2-year follow-up of 287 children aged 9-12 years [47].…”
Section: Discussionmentioning
confidence: 99%
“…Os valores mais elevados podem ser observados dos 15 aos 17 anos (Tabela 4). Estudiosos parecem estar de acordo sobre a relação entre o aumento das idades e a ocorrĂȘncia de dor lombar 12,14,16,34,35,36,37,38 . Tendo em vista esses achados sobre as idades iniciais de ocorrĂȘncia da dor lombar, sugere-se que haja maior atenção em relação Ă  pesquisa, Ă  prevenção e ao tratamento de dor lombar em crianças em jovens, visto que os estudos concluem que sua ocorrĂȘncia na adolescĂȘncia Ă© fator de risco para a dor lombar na vida adulta 7 .…”
Section: Introductionunclassified
“…Studies have shown adults and children with BJHS frequently experience arthralgia, with adults also being prone to generalized back pain. [14][15][16][17][18][19][20][21] There are also some studies that suggest BJHS is associated with fibromyalgia, 22,23 and a prospective cohort study concluded that joint hypermobility in adolescence was a risk factor for musculoskeletal pain at the shoulder, knee, and ankle/foot joints. 24 Research on the conservative treatment of BJHS is quite limited, with most high-level studies (randomized controlled trials) focused on knee pain and lowlevel studies (single-group prospective cohort, case series, case reports) focused on the spine or full body pain.…”
Section: Introductionmentioning
confidence: 99%